DAKWAH PERJUMPAAN BERBASISPEMBELAJARAN MORAL DALAM PERSPEKTIF RECOGNITIVE LEARNING - Ishak Harianto (Universitas Islam Negeri (UIN) Mataram, 2017)
The concept of da’wah does not currently have a clear direction because it has lost its essence. Where the essence of da’wah is missing so far is an invitation towards the path of goodness, delivered with a gentle, without coercion, love, and compassion. The loss, of course, results in the emergence of a skeptical attitude. The essence of the Da’wah that invites towards goodness, delivered with a gentle, without coercion, love, and compassion has been boiled down to the imaging, the sale of the verses of God solely so that aspect of the morality of da’wah is far from what was expected. With regard to the challenge of the propagation, this paper wants to offer moral learningbased encounter Da’wah in the perspective of recognitive learning. Where do Da’wah encounter that could offer in this writing is da’wah as arena encounters a heart because basically, the encounter has a single purpose, namely to unite the hearts and connected Da’wah as arena encounter of hearts, then the means used are emotional and positivity actions speak. In addition to the means of positivity and emotion the language actions of positivity, it is also a moral learning for all individuals, namely learning that leads to changes in the actions of recognitive not just limited to preaching and lectures-lecture of moral cognitive without any change in action.